2019
DOI: 10.21203/rs.2.17094/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dexmedetomidine for prevention of postoperative pulmonary complications in patients after oral and maxillofacial surgery with fibular free flap reconstruction: a prospective, double-blind, randomized, placebo-controlled trial

Abstract: Background: Postoperative pulmonary complications (PPCs) are common and significant problems for oral and maxillofacial surgery patients. Dexmedetomidine (DEX), an α2-adrenoreceptor agonist, has been proven having lung protection effects. However, since now, there has not been final conclusion about whether DEX can reduce the incidence of PPCs. We hypothesize that, in oral and maxillofacial surgery with fibular free flap reconstruction patients, DEX may decrease the incidence of PPCs.Methods: This was a prospe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…18,19 Furthermore, a prospective study reported that dexmedetomidine alleviated subjective pain in oral, maxillofacial, and fibular areas. 20 Even after major surgery involving bone work, the patient necessitated only 48 hours of round-the-clock morphine (2-4 mg every 6 hours) to achieve pain scores of 0 to 3. No agitation was observed even while the patient was kept intubated and the head uncomfortably strapped for several days.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Furthermore, a prospective study reported that dexmedetomidine alleviated subjective pain in oral, maxillofacial, and fibular areas. 20 Even after major surgery involving bone work, the patient necessitated only 48 hours of round-the-clock morphine (2-4 mg every 6 hours) to achieve pain scores of 0 to 3. No agitation was observed even while the patient was kept intubated and the head uncomfortably strapped for several days.…”
Section: Discussionmentioning
confidence: 99%